2-μm band active distributed Bragg reflector laser for CO2 gas sensing. (30th August 2019) - Ueda, Yuta; Shindo, Takahiko; Kanai, Takuya; Shimokozono, Makoto; Fujiwara, Naoki; Ishii, Hiroyuki; Matsuzaki, Hideaki
Abstract: We have developed a 2- μ m-band active distributed Bragg reflector (DBR) laser for CO2 gas sensing employing single quantum well (SQW) gain in the tuning sections. The laser covers the double wavelength band with a <3-dB power penalty during tuning compared with our conventional DBR laser having no active SQW. The absorption-line detection of CO2 gas using the laser is also demonstrated. Furthermore, we show that the ∼60% tuning efficiency for the tuning current of the active DBR laser compared with our conventional one is explained with an assumed rate equation including the carrier consumption for the active SQW gain.